Immunity-Related Gene Signature Identifies Subtypes Benefitting From Adjuvant Chemotherapy or Potentially Responding to PD1/PD-L1 Blockage in Pancreatic Cancer - Qian, Hao; Li, Hongzhe; Xie, Junjie; Lu, Xiongxiong; Li, Fanlu; Wang, Weishen; Tang, Xiaomei; Shi, Minmin; Jiang, Linxi; Li, Hongwei; Chen, Hao; Peng, Chenghong; et al. (Frontiers in Cell and Developmental Biology, 2021)
The tumor microenvironment is not only associated with patient outcomes, but also to the sensitivity of chemotherapy and immune checkpoint blockage. In order to explore mechanism of the tumor immune microenvironment, we constructed an immunity-related 18-gene classifier to classify patients with pancreatic ductal adenocarcinoma (PDAC) into low score and high score groups using The Cancer Genome Atlas (TCGA) PDAC project data. Patients in high score group showed inferior prognosis, which was validated in another four independent cohorts, including Ruijin cohort. High score group showed significant enrichment of pathways involved in cell cycle and cell division, such as G1/S phase transition. IHC analysis revealed higher levels of the proliferative indexes of Ki67 and PCNA in high score group than that in low score group. Prognostic analysis confirmed that patients in high score group could benefit from the gemcitabine-based adjuvant chemotherapy especially targeting G1/S phase. While in low score group, the programmed cell death 1 ligand 1(PD-L1) (+) cases showed T cell infiltration but worse prognosis than PD-L1(-) cases. The immunity-related 18-gene signature could effectively predict prognosis in PDAC. Furthermore, the gene signature might be a practical predictive tool to identify PDAC subtypes benefitting from gemcitabine-based adjuvant chemotherapy or potentially responding to PD1/PD-L1 blockade.